Development of a Biology Learning Module Integrated with Islamic Values to Improve Environmental Care Character - Zuhair Abdullah (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2021)
The low character of environmental care has caused various losses to the environment in Indonesia. On the other hand, education and religion have a big role in shaping human character. On that basis, this study aims to develop a biology learning module integrated with Islamic values that is feasible and effective to improve the environmental care character. The stages of development carried out consisted of eight stages were adapted from the Borg and Gall model. The results showed that the module developed is feasible. Feasibility is proven by the results of the assessment conducted by the validator who obtained a score of 4.3 in the excellent category. The modules have also proven to be effective in improving environmental care character. In a qualitative descriptive analysis, the effectiveness is proved by obtaining the percentage of gain in the treatment class by 58% with the category quite effective and by 33% in the control class with the ineffective category. In a quantitative descriptive analysis, the effectiveness is proved by t-test result with p-value (sig) 0.000 less than 0.05 (Sig < 0.05). It means, there is a significant difference between the gain of environmental care character for the treatment and the control class.